Disparity dilemma - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The persisting ecological constraints of tropical agriculture by Wolfgang Weischet and Cesar Caviedes 1993 336pp ISBN 0 582 05692 6 Longman Scientific & Technical, Longmans Group UK Ltd 5 Bentinck Street London W1M 5RN UK